STAGFLATION IN TURKEY AFTER 2001 - İbrahim Bakırtaş; Ali Tekinşen (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
We observed that simultaneously experienced two undesired thing, namely inflation and unemployment in 2001. In this study, based upon that fact, we try to explain whether or not Turkey experienced this problem defined as stagflation in the literature. In order to test that, we applied structural change test by using ordinary least square OLS method. Our findin indicates that Turkey experienced a structural change in 2001, and long-term Phillips curve shifted to the left, and also unemployment increased in recession for that particular period in Turkey